Post-job Data Analysis by Python for a Miniature Recorder in Drilling Motors. Issue 1 (March 2020) - Li, Fei; Song, Haolan
Abstract: A vibration recorder has been deployed to capture the dynamics data of drilling motors for their operation and health evaluation. The recorder is usually inserted inside the rotor catcher of a conventional drilling motor in such a way that no extra length is introduced to the planned bottom hole assembly (BHA). The recorder can log data over the full operation cycle of a drilling motor, including vibration during surface activities and downhole operation. A post-job data analyzer was specifically designed based on Python. The analyzer processes the recorded data and generates statistics, time plots, and the various statistical plots such as histograms. These statistics and plots help the operators and maintenance technicians to gain insights into the motor operation and performance. The analyzer can provide adequate information on a drilling motor to asset owners for maintenance and operation optimization without analysis training or qualification from operators.